All-optical clock distribution with synchronous frequency division and multiplication - HEGARTY, JOHN (My University, 1992)
A master optical clock from a mode locked laser is distributed to two slave twin section lasers. One slave laser divides the optical modulation frequency by 2, the other slave laser multiplies the frequency by 2. It is also possible to vary the multiplication division ratio in a slave laser using only DC control of the absorber of the twin section laser.
PUBLISHED
Keywords: Physics